Regional Economic Convergence in China: A Comparative Study of Nighttime Light and GDP - Xiao, Qiao-Li; Wang, Yue; Zhou, Wei-Xing (Frontiers in Physics, 2021)
Nighttime lights (NTL) has been used as a proxy for economic growth in recent years. In order to verify the effectiveness of NTL in measuring regional economies, this paper studies the regional economic convergence phenomenon in China's provinces by a comparative analysis of the NTL growth rate and GDP growth rate from 1992 to 2013. It is found that both growth rates exhibit club convergence and the two sets of clubs are relatively consistent. The higher growth rates are concentrated in the central and western regions, while the lower growth rates are concentrated in the eastern and coastal regions. In addition, the growth rate gaps between GDP clubs are relatively flat, while the growth rate gaps between NTL clubs are large. From the perspective of influencing factors of the regional convergence, industrial proportion and service industry ratio are found to have significant effects on the convergence in both cases. For the NTL convergence clubs, the increment of fixed capital, human capital and energy consumption are also significant influencing factors, indicating that NTL, in addition to reflecting the economic activities embodied in GDP, is more responsive to economic activities that are fixed capital-intensive, practitioner-intensive and energy-intensive.